2014
DOI: 10.5121/ijcseit.2014.4101
|View full text |Cite
|
Sign up to set email alerts
|

Web Service Discovery Methods and Techniques: A Review

Abstract: Web Services are independent software systems which offer machine-to-machine interactions over the Internet to achieve well-described operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Another way to create an execution plan is through the automatic disco very of a sequence of services, each responsible for achieving a specific goal. The approach used in [4] involves defining the ontology of each service, based on which the process execu tor finds the optimal path to achieve the desired outcome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way to create an execution plan is through the automatic disco very of a sequence of services, each responsible for achieving a specific goal. The approach used in [4] involves defining the ontology of each service, based on which the process execu tor finds the optimal path to achieve the desired outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Analyzing recent studies and publications [1][2][3][4][5][6], it can be concluded that the process approach to processing economic information is becoming increasingly popular in various TECHNOLOGY AUDIT AND PRODUCTION RESERVES -№ 3/4(71), 2023…”
Section: Introductionmentioning
confidence: 99%
“…The Web Service Discovery method Based on Functional semantics (FBWSD) is a function-based [32,33] service discovery method. The method firstly utilizes the Stanford Parser tool to tokenize the requirement statements and service description texts and then constructs a feature set based on the extracted predicates and objects.…”
Section: Baseline Approachesmentioning
confidence: 99%
“…Discovering services in this method depend on the user's context [27]. Generally, the user context is analyzed to discover the most suitable services.…”
Section: Context-aware Methodsmentioning
confidence: 99%